Mitigation of transverse mode instability through a dynamic modification of the inversion in high-power fiber amplifiers - Stihler, Christoph; Jauregui, Cesar; Kholaif, Sobhy E.; Tu, Yiming; Limpert, Jens (Proceedings of SPIE - The International Society for Optical Engineering, 2021)
Transverse mode instability (TMI) induces detrimental mode coupling in fiber-laser systems at high average powers and still represents the main limitation for the further power scaling of diffraction-limited systems. In this contribution, we describe a new approach to mitigate TMI in fiber amplifiers by dynamically modifying the inversion profile in the fiber. When periodically changing the excitation of the active fiber (e.g. with the help of an acousto-optic deflector), the intensity distribution along the fiber is also dynamically modified. If this is done with a frequency of a few hundreds of kHz (i.e. so that the inversion cannot completely adapt to the new intensity pattern), the inversion grating will be washed out and a homogeneous inversion profile can develop. Consequently, the resulting heat distribution will also be homogenized and the formation of a thermally-induced refractive index grating, which is responsible for the TMI-induced mode coupling, can be largely suppressed. Hence, the presented mitigation approach tackles TMI at an early stage by acting upon the root cause of the detrimental modal energy transfer. At the conference, simulations will be presented which will illustrate the working principle of the new mitigation approach and show its potential to increase the TMI threshold of high-power fiber amplifiers by washing out the inversion profile.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Fiber laser; High power; Mitigation; Mode instability; Population inversion; Refractive index grating; Suppression